Phytochemical analysis and antimicrobial activity from different parts of Plumeria alba - Mohamad Nor, Maryana; Omar, Muhammad Nor; Darnis, Deny Susanti (2010)
Plumeria alba (Apocynaceae) is used in the treatment of ulcers, herpes and scabies. Extraction and phytochemical constituents of different polarity of solvent were investigate for aerial parts (stem, leaf and flower) of Plumeria alba. Soxhlet extraction for hexane, ethyl acetate, dichloro-methane, methanol was perform as well as for aqueous extraction. Phytochemical screening of the crude extract revealed the presence of tannins, saponins, flavonoids, steroids, terpenoids, cardiac glycosides, phytosteroid and reducing sugar in the plants investigated. The antimicrobial activity of crude extract for each solvents were determined using the disc diffusion method for Fusarium solani, Aspergillus niger, Candida albicans, Saccharomyces cerevisae, Pseudomonas aeruginosa, Bacillus subtilis, Bacillus cereus. The results obtained revealed that the ethyl acetate extracts of the flower and leaf was most potent, inhibiting Aspergillus niger, Saccharomyces cerevisae, Pseudomonas aeruginosa, and Bacillus cereus with diameter zones of inhibition ranging from 7mm to 15mm, followed by methanolic extract of the stem and leaf with zone range of 8mm to 11mm, but Bacillus subtilis showed no resistance to the all extract.